(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2021)
This Study Aims At Identifying The Role Of Managerial Leadership In Establishing Business Ethics In The Organization By Adopting The Moral Dimension Of The Administrative Leadership Whose Principles And Principles Derive From The Moral Values Prevailing In Societies, Especially Religion Which Is One Of The Basic Rules Of Values And Ethics. It Was Found That The Leadership Plays An Important Role In Instilling Ethics In The Organization For The Moral Leader To Exert Influence On The Workers, Forming A Model For Them. The Study Recommended That The Dimensions Of Work’s Ethics Should Be Taken Into Consideration Within The Framework Of The Organization’s Culture. Further It Emphasized On Instilling Ethical Leadership Among And Urged Them To Practice More Ethical Behavior Towards Their Work. Keywords: Business Ethics, Ethics, Leadership, Ethical Leadership